2006
DOI: 10.1002/jrs.1588
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Raman microscopy of prehistoric rock paintings from the Sierra de las Cuerdas, Cuenca, Spain

Abstract: Selected pictographs from the prehistoric painting panel 2 of Cueva del Tío Modesto shelter in the Sierra de las Cuerdas (Henarejos, Cuenca, Spain) were studied by Raman microscopy in order to determine the chemical composition of the pigments used. Hematite (a-Fe 2 O 3 ) was found as the main component. The hematite particle size of one motif is much smaller than that observed for the others. No binders were found. A blue-greyish crust extends over the whole panel. Whewellite, weddellite and amorphous carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 31 publications
4
92
0
2
Order By: Relevance
“…The detection of oxalates on the pigments may open a window to date the paintings more accurately, especially if the pigment is encapsulated between two oxalate layers as found for pigments in Spain and Texas, which protect the paint, prevent weathering and have been used for AMS 14 C dating of Post-Paleolithic rock art. 23,24 The origin of the oxalic acid necessary to form the oxalates has been ascribed to previous colonisation of the rock face by lichens, but it has been shown that the presence of rock hyraces in shelters may also be a source of oxalic acid. 17 Furthermore, it is suspected that San artists used plant sap as binder and as many plants have oxalic acid as a constituent of the sap it may have been introduced into the paint in this way as suggested in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of oxalates on the pigments may open a window to date the paintings more accurately, especially if the pigment is encapsulated between two oxalate layers as found for pigments in Spain and Texas, which protect the paint, prevent weathering and have been used for AMS 14 C dating of Post-Paleolithic rock art. 23,24 The origin of the oxalic acid necessary to form the oxalates has been ascribed to previous colonisation of the rock face by lichens, but it has been shown that the presence of rock hyraces in shelters may also be a source of oxalic acid. 17 Furthermore, it is suspected that San artists used plant sap as binder and as many plants have oxalic acid as a constituent of the sap it may have been introduced into the paint in this way as suggested in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…22 The bands around 500 and 524 cm 1 calcite rock faces and has previously also been reported on sandstone. 23,24 In most of the spectra recorded on red parts of the sample, bands at 290, 406, 602 and ¾1300 cm 1 are also present, which are characteristic of haematite. Although it could be expected that iron oxalates would form in the presence of oxalic acid, it was not detected.…”
Section: Red Pigment On Shardmentioning
confidence: 99%
“…Examples of studies concern a wide time span and diverse cultures, from rock art 48,49 and wall paintings 50 -53 (which could also call for the use of mobile measurements) to various supports (paper, 54 -56 wood 57 ). For many of these studies, Raman analysis is involved as a general analytical strategy with complementary measurements as scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS), XRF, laser induced breakdown spectroscopy (LIBS) or XRD.…”
Section: Colours Pigments and Technologiesmentioning
confidence: 99%
“…The characterisation of the composition of the pigments, binders, substrata and accretions, as well as their microstratigraphy and chemical alterations, are the main objectives of this investigation. This information is fundamental to consider potential radiocarbon absolute dating, [14 -19] to investigate degradation processes [9,10,13] and to undertake the appropriate conservation action of the paintings. In the present work, we study the painted panel 3, Fig.…”
Section: Introductionmentioning
confidence: 99%